2018
DOI: 10.3892/etm.2018.6023
|View full text |Cite
|
Sign up to set email alerts
|

Identification and bioinformatics analysis of overlapping differentially expressed genes in depression, papillary thyroid cancer and uterine fibroids

Abstract: It is hypothesized that there may be common characteristics between the genetic regulatory networks of different diseases. To identify these potential similarities, analysis of overlapping differentially expressed genes (DEGs) in several diseases, which are believed to be associated in traditional Chinese medicine (TCM) was performed in the present study. The gene expression profiles associated with depression, papillary thyroid carcinoma (PTC) and uterine fibroids (UF) were preliminarily analyzed using Gene E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…P values < 0.05 were considered statistically significant. GO and KEGG analyses were used to perform a comprehensive functional analysis of DEGs in the DG and ACC [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…P values < 0.05 were considered statistically significant. GO and KEGG analyses were used to perform a comprehensive functional analysis of DEGs in the DG and ACC [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…The datasets were standardized, normalized by TPM (Transcripts Per Kilobase Million) and log transformed to identify DEGs with respect to the diseased vs control samples. In this study, the genes with log2FC > 1.5 and P value < 0.05 were defined as DEGs ( 25 , 26 ). The datasets were examined both individually and in groups to identify the genes unique to the respective diseases.…”
Section: Methodsmentioning
confidence: 99%
“…According to data published by the World Health Organization, the prevalence of depression worldwide is about 3% [24], and the prevalence of depression in patients with papillary thyroid cancer is as high as 30% [25]. A retrospective study by British scholars found that major depression may increase the incidence of thyroid disease [26].…”
Section: Papillary Thyroid Carcinoma and Serotonin Transporter Genementioning
confidence: 99%